Tomorrow's Manpower Needs. National Manpower Projections and a Guide to Their Use as a Tool in Developing State and Area Manpower Projections - Bureau of Labor Statistics (DOL), Washington, DC.; Bureau of Labor Statistics (DOL), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
This report provides employment by industry for 1960 and 1969, with projections for 1975. The second part of the report presents guidelines for developing state and area employment estimates for 1960 and 1975. The report concludes with a discussion of labor supply and demand and their interrelationship. This supplement presents revised employment projections superseding the data in earlier volumes, which are available as ED 032 398-032 401. (BH)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Employment Projections; Employment Statistics; Labor Needs; Research Methodology; Tables (Data)